BIOPHYSICAL EXPERIMENTS WITH ISES SYSTEM - SCANNING (MEASUREMENT) OF BIOLOGICAL SIGNALS OF HUMAN BODY - BALEK, Bronislav (Trends in education, 2011)
Inteligent School Experimental System (ISES) is computer system which also we can use in biophysics for scanning and procesing of biological signals of human body.
Keywords: biophysics; experiments; ISES; biosignal; human body.